Building back better children's surgical services toward universal health coverage: Perspectives from Bangladesh and Zimbabwe - Mazingi, Dennis; Chowdhury, Tanvir Kabir; Aziz, Tasmiah Tahera; Tamanna, Nowrin; Lakhoo, Kokila; Banu, Tahmina; Mustafa, Saqif (Frontiers in Public Health, 2023)
Introduction This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict’. Children's surgical services are crucial, yet underappreciated, for children's health and must be sufficiently addressed to make and sustain progress toward universal health coverage (UHC). Despite their considerable burden and socioeconomic cost, surgical diseases have been relatively neglected in favor of communicable diseases living up to their inauspicious moniker: ‘the neglected stepchild of global health'. This article aims to raise awareness around children's surgical diseases and offers perspectives from two prototypical LMICs on strengthening surgical services in the context of health systems recovery following the COVID-19 experience to make and sustain progress toward UHC. Approach We used a focused literature review supplemented by the perspectives of local experts and the 6-components framework for surgical systems planning to present two case studies of Bangladesh and Zimbabwe. The lived experiences of the authors are used to describe the impact of COVID-19 on respective surgical systems and offer perspectives on building back the health system and recovering essential health services for sustainability and resilience. Findings We found that limited high-level policy and planning instruments, an overburdened and under-resourced health and allied workforce, underdeveloped surgical infrastructure (from key utilities to essential medical products), lack of locally generated research, and the specter of prohibitively high out-of-pocket costs for children's surgery are common challenges in both countries that have been exacerbated by the COVID-19 pandemic. Discussion Continued chronic underinvestment and inattention to children's surgical diseases coupled with the devastating effect of the COVID-19 pandemic threaten progress toward key global health objectives. Urgent attention and investment in the context of health systems recovery is needed from policy to practice levels to improve infrastructure; attract, retain and train the surgical and allied health workforce; and improve service delivery access with equity considerations to meet the 2030 Lancet Commission goals, and make and sustain progress toward UHC and the SDGs.